(untitled) (Damascus University Journal of agriculture sciences, 2026)
The research was carried out in the biodiversity laboratory and greenhouse of the national commision for Biotechnology and the laboratory of plant bacterial diseases-Faculty of Agriculture- Damascus University during the years 2022-2023 with the aim of studying the laboratory antagonistic ability of locally isolated rhizobia bacteria against Fusarium oxysporum f. sp. ciceris fungus that cause of chickpea vascular wilt, which is also isolated locally. 61 bacterial isolates were used, 42 of them were identified as belonging to the rhizobia group (Rhizobium, Mesorhizobium, Bradyrhizobium, Ensifer), while two fungal isolates were obtained from Fusarium of chickpea, isolated and identified locally (F51 and F63) in albaath university, plant protection department. The antagonistic ability of the bacterial isolates was tested in the laboratory using the strip method, and 31 isolates showed their ability to inhibit fungal growth for both fusarium isolates, including 13 isolates from the rhizobia group and 18 isolates of unidentified rhizobacteria. Isolates 134 and 133 (Rhizobium) outperformed the rest of the isolates in inhibiting the fungus F63, isolate inhibition rates 68.89% and 65.93%, respectively, while isolate 61 (Mesorhizobium) excelled against the fungus isolate F51, and the inhibition rate reached 53.70%. When the three isolates were tested in the pots (134,133 on vicia faba and 61 on ciceri arietinum), In comparison between the two treatments: fungus*bacteria (F63*133, F63*134, F51*133, and F51*134) and the two treatments: fungus only (control F63 and control F51), the results showed that inoculation with bacterial isolates significantly increased the plant’s tolerance to vascular wilt, as the severity of the disease and the infection rate decreased significantly. Growth indicators also increased, and no significant differences appeared between the effect of the two bacterial isolates on the disease incidence and severity. In comparison between the two treatments (F63*61 and F51*61) and the controls (F63 and F51), there was a significant difference, and the bacterial treatment increased some growth indicators (shoot and root fresh and dry weight) and reduced the infection rate and disease severity. Our results indicate the usefullness of inoculating legums seed with appropriate rhizobia isolates, not only to improve growth indicators, but also to strengthen crop protection against Fusarium vascular wilt. .